The Impact of Using Digital Filter and Analog Filter on EMG Signal - Setioningsih, Endang Dian (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2019)
Many cases of accidents which resulted in humans having to surgery to save them, then performend muscle therapy to help the patient’s recovery after going through the post-surgery. This therapy has a purpose, so that the patient’s body is expected to return to normal. An exoskeleton is a tool like an additional clothing that aims not only to protect, but also to increase the wearer's abilities. Electromyography (EMG) is a technique for evaluating and recording the electrical activity produced by skeletal muscles. The purpose of this study was to analyze the differences in the use of analog and digital filters on EMG, as well as the effect on the exoskeleton simulation. The method used in the main design consists of the myoware module, notch circuit, low pass filter, arduino uno, DAC module, teraterm software, and matlab. The intercepted signal is taken from the biceps using a disposable electrode (AG/AGCL.). The EMG signal tapped by the myoware module will continue to another circuit, then recorded on the Teraterm software, and analyzed in MATLAB. The voltage value on the analog filter is 1.541 Volt during relaxation and 2.086 Volt during contraction, while the digital filter that has passed through the DAC has a value of 41.8 mVolt during relaxation and 269.1 mVolt during contraction. The results of this study obtained that digital and analog filter values ​​have an average difference of 5 to 30. The conclusion of this research tool can detect changes in the use of analog and digital filters, in the future research can be developed by comparing other types of digital filters along with replacement to wireless systems. The benefit or purpose of this research is as a simulation of exoskeleton skeletal motion and can see the difference between the use of digital and analog filters